Data-driven historical characterization of epilepsy-associated genes. (January 2023) - Macnee, Marie; Pérez-Palma, Eduardo; López-Rivera, Javier A.; Ivaniuk, Alina; May, Patrick; Møller, Rikke S.; Lal, Dennis
Abstract: Many epilepsy-associated genes have been identified over the last three decades, revealing a remarkable molecular heterogeneity with the shared outcome of recurrent seizures. Information about the genetic landscape of epilepsies is scattered throughout the literature and answering the simple question of how many genes are associated with epilepsy is not straightforward. Here, we present a computationally driven analytical review of epilepsy-associated genes using the complete scientific literature in PubMed. Based on our search criteria, we identified a total of 738 epilepsy-associated genes. We further classified these genes into two Tiers. A broad gene list of 738 epilepsy-associated genes (Tier 2) and a narrow gene list composed of 143 epilepsy-associated genes (Tier 1). Our search criteria do not reflect the degree of association. The average yearly number of identified epilepsy-associated genes between 1992 and 2021 was 4.8. However, most of these genes were only identified in the last decade (2010–2019). Ion channels represent the largest class of epilepsy-associated genes. For many of these, both gain- and loss-of-function effects have been associated with epilepsy in recent years. We identify 28 genes frequently reported with heterogenous variant effects which should be considered for variant interpretation. Overall, our study provides an updated and manually curated list of epilepsy-related genes together with additional annotations and classifications reflecting the current genetic landscape of epilepsy. Highlights: We present a computationally driven review of epilepsy-associated genes using the literature available in PubMed. We identify 738 Tier 2 and an additional subset of 143 Tier 1 epilepsy genes that were manually curated. Ion channels represent the largest class of epilepsy-associated genes. For many of these, both gain- and loss-of-function effects have been associated with epilepsy in recent years. Overall, our study provides a data-driven overview of the past and current genetic landscape of epilepsy. Abstract : We present a computationally driven review of epilepsy-associated genes using the complete scientific literature available in PubMed. We identify 738 Tier 2 and an additional subset of 143 Tier 1 epilepsy genes that were manually curated. The majority of associations were made in the last decade. We also identify 28 genes frequently reported with heterogenous variant effects which should be considered for variant interpretation. Ion channels represent the largest class of epilepsy-associated genes. For many of these, both gain- and loss-of-function effects have been associated with epilepsy in recent years. Overall, our study provides a data-driven overview of the past and current genetic landscape of epilepsy.